Towards Setting Indicators and Criteria for Evaluating Arab Publishing Periodicals - Fahem, Said; Madani, Imene (LANGUAGE ART, 2021)
Scientific publishing is one of the cornerstones of the universities; and it is dependent on the educational process, especially in the field of teaching, as well as scientific communication between researchers. The quality of research and its relevance to development issues, the diversity of its outputs and results, and the ways of making it available, for that we think that there is no use of science unless it is published, and made available to serve the community. The most important aspect of the university’s job is to publish the results of scientific research in the form of articles and research in scientific and specialized scientific instruments, books, and scientific works published by international publishing houses. It has a long tradition of publication, printing, distribution, cataloguing and inclusion in recognized databases or research papers in scientific conferences and other scientific research outputs. If universities and academic institutions succeed in the two functions mentioned above - education and research - this will inevitably reflect on the third job, namely the service of development and have a positive impact on the economy and social aspects. The competition between universities and scientific academic bodies to increase the status of publishing in solid and indexed journals has intensified in global platforms due to the adoption of the outputs of scientific research of all kinds of the most important standards in the International Classification of Universities, especially those publications whose quotation has increased. To explore the quality of such research, some scientific institutions have established a platforms, measurement tools, indicators and databases to evaluate these journals and verify their compliance with academic standards. This research is carried out by monitoring some of the scientific institutional efforts to evaluate the Arab periodicals. We have consulted three models: Algerian Scientific Journal platform (ASJP), Al-Manhal and the Arab impact factor, and we conclude the research with a number of conclusions and recommendations.